Effect of Phosphorus on Nutrient Uptake of Japonica and Indica Rice (Journal of Agriculture & Rural Development, 2008)
An experiment was conducted at the screen house of Tsukuba International Centre (TBIC), Japan to clarify the effect of phosphorus on nutrient absorption characteristics of a japonica (Nipponbare) and an indica (IR-28) rice variety. The experiment was conducted under submerged condition in subsoil of an Andisol, which had a high capacity of phosphate fixation. Levels of phosphorus were 100, 200, 500 and 800 kg P2O5 ha-1. The P content in rice plant at different growth stages increased progressively with an increase of P levels for both the varieties. With respect to P content, varietal differences were minimal. But in the case of N and K content, IR-28 showed higher ability than Nipponbare. At maximum tillering stage, both the varieties showed negative co-relation between P and N uptake but at harvest stage, strong positive co-relation between P and N uptake was found for both the varieties. Both the varieties showed positive co-relation between N and K uptake at all the stages. Key words: Andisol, IR-28, nipponbare, phosphorus, uptake. doi:10.3329/jard.v6i1.1651 J Agric Rural Dev 6(1&2), 7-12, June 2008